MENCIPTAKAN POSITIVE WORD OF MOUTH INTENTION MELALUI REPUTASI, KEPUASAN RELASIONAL DAN CUSTOMER-COMPANY IDENTIFICATION - Nunung Ghoniyah (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2013)
Word of mouth (WOM) intentions plays an important role in influencing attitudes and behavior. The use of WOM in marketing strategies are increasing with the development of internet technology was allowing people to spread on to others. Consumers are more willing to do WOM if well-regarded corporate reputation, they are satisfied with their relationship with the company and they feel proximity with company.